Chemical precipitation enabled UF and MF filtration for lead removal. (June 2021) - Xu, Zitong; Gu, Siwei; Rana, Dipak; Matsuura, Takeshi; Lan, Christopher Q.
Graphical abstract: Highlights: CPEMF an effective technology for lead removal from water. pH, DIC, and membrane the three key parameters in CPEMF. Optimal Pb(II) removal 99.8 % at 5 ppm with 7150 kg m −2 h −1 flux using MF at 15 psig. Size rejection the major mechanism of chemical filtration. Abstract: In this study, the removal of Pb 2+ ions by chemical precipitation enabled membrane filtration (CPEMF) was investigated. Two different membranes, i.e., microfiltration (MF) and ultrafiltration (UF), and five different dissolved inorganic carbon (DIC) i.e., 0, 0.5, 1, 2, and 4 mM, were tested for this purpose at three different pH levels, i.e., pH 7.5, pH 8.5, and pH 10.0. The performance of CPEMF was evaluated by measuring the flux, the lead concentration in the permeate. The Zeta potential and morphology of particles in feed under different conditions were characterized by transmission electron microscopy (TEM) and particle size distribution. It was established that under the optimal conditions, i.e., 1 mM DIC and pH 8.5, the permeate lead level could be brought to below the drinking water standard, i.e., 10 ppb, when the feed contained 5 ppm Pb 2+ . Mechanisms of CPEMF were discussed based on experimental evidence.